1999
DOI: 10.1007/s004390050972
|View full text |Cite
|
Sign up to set email alerts
|

The mutation spectrum of the bestrophin protein - functional implications

Abstract: Best's macular dystrophy (BMD), also known as vitelliform macular degeneration type 2 (VMD2; OMIM 153700), is an autosomal dominant form of macular degeneration with mainly juvenile onset. BMD is characterized by the accumulation of lipofuscin within and beneath the retinal pigment epithelium. The gene causing the disease has been localized to 11q13 by recombination breakpoint mapping. Recently, we have identified the causative gene encoding a protein named bestrophin, and mutations have been found mainly to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 18 publications
1
59
0
Order By: Relevance
“…8 Two additional Danish families were reported by Bakall et al in 1999 (Table 1). 11 Patients with Best disease identified in the present study demonstrated a variable clinical appearance, ranging from precipitate-like alterations at the level of the photoreceptor outer segments to choroidal neovascularization. The findings thus exceeded those reported recently in asymptomatic patients with Best disease, in whom a subtle thickening was demonstrated by SD-OCT between the retinal pigment epithelium and the photoreceptors.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…8 Two additional Danish families were reported by Bakall et al in 1999 (Table 1). 11 Patients with Best disease identified in the present study demonstrated a variable clinical appearance, ranging from precipitate-like alterations at the level of the photoreceptor outer segments to choroidal neovascularization. The findings thus exceeded those reported recently in asymptomatic patients with Best disease, in whom a subtle thickening was demonstrated by SD-OCT between the retinal pigment epithelium and the photoreceptors.…”
Section: Discussionmentioning
confidence: 65%
“…8,[11][12][13][14][15][16] In the present study, sequencing analysis of all BEST1 exons revealed heterozygous missense changes that are likely pathogenic in all eight analyzed families as well as one sporadic case (Fig. 2, Supplemental material at AJO.com or Supplemental Fig.…”
Section: Mutation Analysismentioning
confidence: 85%
“…6,[11][12][13][14][15][16] Recently, the VMD2 gene was identified by positional cloning, and thus far 29 different disease-related mutations have been described. [17][18][19][20] VMD2 is RPE-specific and is comprised of 11 exons coding for a 585 amino acid protein of unknown function. The identification of the disease gene now facilitates research aimed at understanding the pathogenetic mechanism underlying Best disease.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, is not inconsistent with previously identified mutations (p.Gly135Ser). 41,42 Despite specific clustering of VMD mutations within BEST1, clear genotype-phenotype correlations are yet to be established for VMD. However, a recent study by a Dutch group purported a severe disease phenotype in one family with a Ala10Val mutation.…”
Section: Mutationmentioning
confidence: 99%